2016
DOI: 10.1371/journal.pone.0168795
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of EGFR Mutations among 1506 Cases of Non-Small Cell Lung Cancer Patients in Guangxi, China

Abstract: An association between epidermal growth factor receptor (EGFR) and clinical characteristics of non-small cell lung cancer (NSCLC) was reported ten years ago. In addition, a different type of relationship was seen in different ethic races. However, the relationship between these factors is not well understood in the Guangxi province. Up to now, there are only very limited data on the association of TTF1/EGFR protein positivity and EGFR mutation status in NSCLC. This study aims to investigate the role of EGFR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 37 publications
5
25
3
Order By: Relevance
“…Next, in our clinical study, we observed a high clinical sensitivity (82.0%) and specificity (100%) of ADx-SuperARMS EGFR mutation blood testing. E19Dels and L858R were the two most common EGFR mutation subtypes in our study, just as reported in previous Chinese NSCLC studies[ 47 , 48 ]. Compared to the performance of ddPCR[ 30 ], ADx-SuperARMS provides a better sensitivity of E19Dels (88% vs. 82%) and L858R (89% vs. 80%) mutation detection in plasma with a specificity of 99% and 100% respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Next, in our clinical study, we observed a high clinical sensitivity (82.0%) and specificity (100%) of ADx-SuperARMS EGFR mutation blood testing. E19Dels and L858R were the two most common EGFR mutation subtypes in our study, just as reported in previous Chinese NSCLC studies[ 47 , 48 ]. Compared to the performance of ddPCR[ 30 ], ADx-SuperARMS provides a better sensitivity of E19Dels (88% vs. 82%) and L858R (89% vs. 80%) mutation detection in plasma with a specificity of 99% and 100% respectively.…”
Section: Discussionsupporting
confidence: 89%
“…To analyze the relationship between the demographic and clinicopathological data with gene mutations can reveal the clinical characteristics of patients with mutations and provide references for clinical diagnosis and treatment. As it was reported that histology and smoking status are associated with EGFR status [24] , which was proved in our study. For gender, previous studies indicated that the detection rate of EGFR mutations in women was higher, partly due to the higher proportion of non-smokers in the female population.…”
Section: Discussionsupporting
confidence: 86%
“…For gender, previous studies indicated that the detection rate of EGFR mutations in women was higher, partly due to the higher proportion of non-smokers in the female population. [24,25] In the present study, female patients had a higher incidence of common mutations than those with rare mutations. Rare mutations occurred more frequently in male patients.…”
Section: Discussionsupporting
confidence: 40%
“…Common features of never-smokers with NSCLC have been identified, including East Asian ethnicity, female sex, adenocarcinoma (specifically bronchoalveolar) pathology, and an increased likelihood of EGFR mutations, which may result in different therapy choices. 38,104 The availability of anti-EGFR and anti-ALK therapies and an anticipation for new drugs have led to the introduction of a 'lung panel' diagnostic system where patients' biopsy samples are tested for mutations like EGFR, ALK and K-RAS before consultation with oncologists. 105 Cytotoxic chemotherapy is unlikely to be removed from the pathway completely and, for selected patients, will most likely continue to provide palliative benefit.…”
Section: Lung Cancer Treatment and Molecular Targetsmentioning
confidence: 99%